2005
DOI: 10.1007/s11661-005-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of Sr-rich intermetallic particles and their influence on pore formation in Sr-modified A356 alloy

Abstract: The nature of enhanced pore formation in Sr-modified A356 Al alloy melts has been investigated, leading to the observation of the precipitation of Sr-rich compounds on the wetted side of oxide films. Scanning electron microscopy of casting surfaces showed that the surface oxide film might be a good possible nucleation site of Sr-rich compounds. The observation of internal pores using secondary electron microscopy and X-ray microanalysis mapping showed precipitation of Sr-rich compounds on the wetted side of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…1 ' 67 Modifiers can, however, also increase inclusion content in the melt through the formation of Sr oxides, as well as decrease the surface tension, and increase the freezing range of the alloys. 68 ' 69 Consequently, the addition of Sr is frequently associated with an increase in the amount of porosity.…”
Section: Modificationmentioning
confidence: 99%
“…1 ' 67 Modifiers can, however, also increase inclusion content in the melt through the formation of Sr oxides, as well as decrease the surface tension, and increase the freezing range of the alloys. 68 ' 69 Consequently, the addition of Sr is frequently associated with an increase in the amount of porosity.…”
Section: Modificationmentioning
confidence: 99%
“…These intermetallic compounds might be nucleated on a bifilm defect. Miresmaeili [26] calculated the lattice mismatch between MgAl 2 O 4 spinel and Al 2 Si 2 Sr to be 4.26 pct, and suggested that spinel could be a favored nucleation site for the growth of intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the issue of the dynamical interaction between melt and the soft oxide layer that encases the solidifying sample should deserve specific attention. This is, of course, a recurrent, open question in aluminium alloy casting [21,22].…”
Section: Discussionmentioning
confidence: 99%